Yuxtaposición narrativa a través de la metaficción: análisis comparativo de La rosa púrpura de El Cairo y Matrix Resurrections - Dra. María Jesús CABELLO BUSTOS (Fonseca, Journal of Communication, 2023)
One of the characteristics that defines Woody Allen's cinema are the references to the seventh art. His characters are constantly seen going to cinematographic projections. Undoubtedly, the most iconic of these situations in his filmography occurs in The Purple Rose of Cairo (1985), where the reality-fiction dichotomy merges, with the characters transcending their respective narratives.